Nilai Ekonomi Ayam Kampung IPB-D1 diberi Larutan Eco-enzyme - Lasa Lado, Florianus; Luruk, Maria Yasinta; Suryatni, Ni Putu Febri (Animal Agricultura, 2025)
The aim of this research is to identify and analyze the economic performance of the IPB-D1 chicken farming business. The method used in the research was an experimental method using a Completely Randomized Design (CRD) which consisted of 4 treatments with 6 replications resulting in 24 experimental units and each replication used 3 IPB-D1 chickens. The treatments given in this study were P0: 1 liter of drinking water without eco-enzyme, P1: 1 liter of drinking water + 1 cc of eco enzyme, P2: 1 liter of drinking water + 2 cc of eco enzyme, P3: 1 liter of drinking water + 3 cc ecoenzyme. The variables measured are production costs, revenues, income, profits, IOFC, R/C . The research results showed that the treatment had no significant effect on economic value (P>0.05). It was concluded that the provision of eco enzyme had the same effect on the economic value of IPB-D1 native chicken.